Assessment of knowledge, attitude, and practice of self-medication among college students - Uppal, Dipan; Agarwal, Monika; Roy, Vandana (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Self-medication is widely practiced both in developed and developing countries. Self-medication has certain advantages as it is convenient, economical, and medical resources are not wasted for minor illnesses. However, there are disadvantages as the disease recognized may not be correct, there is delay in meeting a health care worker, the side-effects of the medication are not known, inappropriate usage of antibiotics leading to drug resistance, taking the same drug with different trade names, it can lead to drug interactions and can also lead to drug addiction. College students prefer self-medication for minor illness or to save time and money. There is no data on the prevalence and pattern of self-medication in college students in Delhi. The objective of this study was to assess knowledge, attitude, and practice of self-medication among medical and non-medical students. Methods: A cross-sectional study was carried out in 200 students of Delhi University using a pretested, structured questionnaire about demographics, knowledge, attitude, and practices of self-medication. Statistical analysis was done using SPSS version 16.0. Results: Self-medication is commonly practiced among both medical and non‑medical college students. From a total of 200 students, 93% of the students had used self-medication of which 7% used it always. Allopathy is the most preferred system of medication. Conclusions: The reasons for self-medication were similar among medical and non-medical students, but positive attitude and knowledge toward self-medication was more among the medical students.